Market threads : how cotton farmers and traders create a global commodity - Çalışkan, Koray, 1972- (The Princeton economic history of the Western world Understanding the process of economic change, 2010)
What is a global market? How does it work? At a time when new crises in world markets cannot be satisfactorily resolved through old ideas, Market Threads presents a detailed analysis of the international cotton trade and argues for a novel and groundbreaking understanding of global markets. The book examines the arrangements, institutions, and power relations on which cotton trading and production depend, and provides an alternative approach to the analysis of pricing mechanisms. Drawing upon research from such diverse places as the New York Board of Trade and the Turkish and Egyptian countrysides, the book explores how market agents from peasants to global merchants negotiate, accept, reject, resist, reproduce, understand, and misunderstand a global market. The book demonstrates that policymakers and researchers must focus on the specific practices of market maintenance in order to know how they operate. Markets do not simply emerge as a relationship among self-interested buyers and sellers, governed by appropriate economic institutions. Nor are they just social networks embedded in wider economic social structures. Rather, global markets are maintained through daily interventions, the production of prosthetic prices, and the waging of struggles among those who produce and exchange commodities. The book illustrates the crucial consequences that these ideas have on economic reform projects and market studies. --From publisher's description.